PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 004 PETAPAHAN - Mona Monita; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research was mathematic learning outcomes in fourth grade (IV) students SDN 004 Petapahan still low with average value 60,14 (with KKM 70). The purpose of this research was to improve mathematic learning outcomes of the fifth grade (V) students SDN 004 Petapahan with the implementation of cooperatif’s make a match type learning model. This research was classroom action research with two cycles. The subjects were students of class V SDN 004 Petapahan academic years 2015/2016 which amounted to 36 people consisting of 16 women and 20 men. Based on the result a discussion the observation of teacher’s and student activity sheet seen rising each meeting. Teacher’s activity with the implementation of cooperatif’s make a match type learning model at first meeting of first cycle was 61,67% (good), and second meeting was 70,00% (good). At second cycle, teacher’s activity at first meeting was 80,00% (good) and second meeting was 93,33% (very good). Students activities at first meeting of first cycle was 53,33% (enough) and second meeting was 63,33% (good). At second cycle, students activities at first meeting was 68,33% (good), second meeting was 78,33% (very good). Mathematic learning outcomes before implementation cooperatif’s make a match type learning model average 60,14, after implementation of cooperatif’s make a match type learning model UH I was 62,50 that improve 3,92%, UH II was 71,91 that improve 19,41%. Implementation of cooperatif’s make a match type learning model can improved mathematic learning outcomes of the fifth grade (V) students SDN 004 Petapahan.Key Words: Cooperatif’s make a match type learning model, mathematic studies studentsachievement